Further Evidence for the ∼9 s Pulsation in LS 5039 from NuSTAR and ASCA - Kazuo Makishima; Nagomi Uchida; Hiroki Yoneda; Teruaki Enoto; Tadayuki Takahashi (The Astrophysical Journal, 2023)
The present study aims to reinforce the evidence for the ∼9 s pulsation in the gamma-ray binary LS 5039, derived from a Suzaku observation in 2007 and a NuSTAR observation in 2016. Through a reanalysis of the NuSTAR data incorporating the orbital Doppler correction, the 9.0538 s pulsation was confirmed successfully even in the 3–10 keV range, where it was undetectable previously. This was attained by perceiving an energy-dependent drift in the pulse phase below 10 keV and correcting the pulse timing of individual photons for that effect. Similarly, an archival 0.7–12 keV data set of LS 5039, taken with the ASCA Gas Imaging Spectrometer in 1999 October, was analyzed. The data showed possible periodicity at about 8.882 s, but again the energy-dependent phase drift was noticed below 10 keV. By correcting for this effect, and for the orbital Doppler delays in the LS 5039 system, the 2.8–12 keV periodicity became statistically significant at 8.891 ± 0.001 s. The periods measured with ASCA, Suzaku, and NuSTAR approximately follow an average period derivative of $\dot{P}≈ 3.0× {10}^{-10}$ s s ^−1 . These results provide further evidence for the pulsation in this object and strengthen the scenario proposed by Yoneda et al. that the compact object in LS 5039 is a strongly magnetized neutron star.